Deliberatization Politic Exposition about Democracy - Hari, Hari; Sahruddin, Sahruddin; Zulkarnain, Zulkarnain (Budapest International Research and Critics University, 2022)
During the political liberalisation of the reform era (1998 – present), various groups have complained about the evil practices of democratic politics. One of the shooting targets is that we have made the wrong choice, namely adopting a majoritarian or liberal democracy model. In the literature on democracy theory, one of the theories relevant to improving democratic practice is TDD (Theory of Deliberalization of Democracy). Although still using the principle of representation, TDD, in general, makes corrections or improvements to the procedures and substance of democracy that have been poorly practised in Indonesia today. This research is based on qualitative research using the descriptive-analytical method to provide a clear picture of the object of the problem. The conclusion of this study shows evidence that there is a model of democracy—both in substance and in procedures. They are different from the mechanism of representation initially derived from the theory of representative democracy.